BAKUNTAU SEBAGAI PRAKTIK BUDAYA INDIGENOUS: KAJIAN FILOSOFIS TENTANG IDENTITAS DAN NILAI PENDIDIKAN ISLAM - Reza Setya Rachman; Nuril Khasyi’in; Sheila Rosalia; Mutia Rahmawati (STIT Darul Hijrah Martapura, 2026)
This study explores the philosophy, identity, and Islamic educational values embedded in Bakuntau, a traditional martial art of the Banjar community in South Kalimantan. Rather than viewing Bakuntau solely as a combat heritage, this research positions it as a form of cultural pedagogy that fosters character building and spiritual development. In the context of modernization and globalization, Bakuntau faces challenges such as value shifts, cultural commodification, and declining youth interest, which may reduce its educational meaning to mere performance or sport. To address this, Islamic educational values are operationalized as observable practices, including tawhid, adab, discipline, self-control, ukhuwah, gratitude, and ethical responsibility in martial practice. Using a qualitative descriptive method with an ethnographic approach, data were collected through literature review and in-depth interviews with two Banjar Kuntau practitioners, and analyzed thematically. The findings reveal that Bakuntau reflects a balance between physical strength and inner spirituality, functioning as a medium for internalizing Islamic values while reinforcing Banjar cultural identity. This study emphasizes that Bakuntau should be preserved not only as martial techniques but also as a value-based educational practice relevant to contemporary society.